Dietary data of a highly biodiverse anuran assemblage in the Ecuadorian Amazon - Menéndez-Guerrero, Pablo (2022)
This dataset reports the diet composition of a highly diverse anuran assemblage in the Ecuadorian Amazon region. In 2001 we examined the diet of an assemblage of frogs from Yasuní National Park. We describe the diet of 396 adult individuals, belonging to 35 species, based on their gastrointestinal contents. Using a stereoscopic microscope, we were able to identify 4085 prey items, and classified them in 71 categories. Also, we used a digital caliper to measure the size and estimate the volume of prey items that were found intact. In addition to diet composition, we provide information of all specimens that were examined including, museum number, family name, species name, and place and date of collection. Finally, we present an anuran–prey interaction network figure to visualize species interactions. This is the first report of the diet composition of an anuran assemblage from Yasuní National Park. It contributes to the understanding of trophic ecology of frog assemblages and the functional role of frogs in Amazonian ecosystems. In addition, our dataset helps to fill the great knowledge gap that exists about ecological interactions in the tropics.